Peningkatan Literasi Siswa SMA Negeri 1 Bone Pantai : Sosialisasi terkait Aplikasi Informasi Kebencanaan sebagai Penguatan Tanggap Terhadap Bencana - Ninasafitri, Ninasafitri; Eraku, Sunarty Suly; Melo, Ramla Hartini; Aris, Ayub Pratama; Masruroh, Masruroh; Pambudi, Moch. Rio (Damhil: Jurnal Pengabdian kepada Masyarakat, 2024)
Indonesia, which is located in an area prone to natural disasters such as earthquakes and tsunamis, requires an increase in disaster literacy, especially in Gorontalo Province. This service aims to improve disaster literacy at SMA Negeri 1 Bone Pantai through socialization and training on the use of disaster information applications. The service method includes socialization, practical training with simulation of emergency situations, as well as pre-test and post-test evaluation of student knowledge. The results showed a significant increase in students' understanding of disaster types, use of disaster applications, and preparedness in responding to disasters. Assistance by lecturers and integration of the program in the school curriculum as well as the formation of a disaster volunteer group are expected to ensure the sustainability of improving disaster literacy at SMA Negeri 1 Bone Pantai.